The sum of the three given numbers = n + m + (n-m) = 2n is even.
Hence all three cannot be odd.
Hence their product is even
Prove that the number nm(n-m) is even for any integers n & m
odd*even=even
Case 1,
If n and m are both even.
nm is even and n-m is even
So, nm(n-m) is also even.
Case2,
If 1 is odd and the other is even
nm is even. n-m is odd
so, nm(n-m) is even.
Case3,
If both are odd.
nm is odd. n-m is even
again nm(n-m) is even.
Hence proved. :)
The sum of the three given numbers = n + m + (n-m) = 2n is even.
Hence all three cannot be odd.
Hence their product is even